Lithium ion battery silicon-carbon negative electrode material and preparation method thereof

The silicon-carbon anode material prepared through high-speed centrifugal spray drying technology, combined with coating technology, solves battery performance problems caused by volume changes in the silicon anode material, significantly improves the cycle stability and service life of the battery, and reduces production costs.

CN119340365APending Publication Date: 2025-01-21SHENZHEN GUANGFENG NEW ENERGY TECH INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411468006.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The volume of the silicon negative electrode material in lithium-ion batteries varies greatly during the lithium-embedding/deliquefaction process, resulting in cracking, instability of SEI film, and consumption of active lithium ions, which in turn affects battery capacity and Coulomb efficiency.

Method used

Use high -speed centrifugal spray drying technology to prepare silicon carbon negative materials. By dispersing nano -silicon, graphite, and adhesives in water -free ethanol to form silicon carbon plasma, then spray drying and granules, and finally use asphalt powder or phenolic resin Powder is covered to form a stable negative material.

Benefits of technology

It significantly improves the cycle stability and service life of the battery, alleviates the volume expansion of silicon materials in the charging and discharge process, reduces production costs, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340365A_ABST
    Figure CN119340365A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion battery silicon-carbon negative electrode material and a preparation method thereof.The preparation method comprises the steps that nanometer silicon slurry, graphite and a binder are evenly dispersed in absolute ethyl alcohol according to a certain mass percent, and silicon-carbon slurry is obtained; carrying out spray drying on the silicon-carbon slurry to obtain silicon-carbon mixed particles; and mixing the silicon-carbon mixed particles with any one of asphalt powder or phenolic resin powder, coating in inert gas, and crushing and screening the coated silicon-carbon material to obtain the lithium ion battery silicon-carbon negative electrode material. The prepared silicon-carbon negative electrode material for the lithium ion battery is stable and reliable in quality, the overall performance of the battery is remarkably improved, and meanwhile the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of society, the demand for energy is increasing, prompting the new energy field to continuously explore technologies that convert various types of energy into electrical energy and store it in batteries. Lithium-ion battery technology is one of the core technologies for new energy storage and conversion. At present, electric vehicles mainly use lithium-ion batteries for electric propulsion. Compared with lead-acid batteries and nickel-hydrogen batteries, lithium-ion batteries have the advantages of high energy density, good cyclability, high coulomb efficiency, safety, and low environmental pollution. Therefore, lithium-ion batteries have been widely used in mobile electronic devices and are constantly developing in electric vehicles, with broad application prospects.

[0003] The specific capacity of a battery is determined by the specific capacity of the negative electrode and positive electrode materials. As one of the key factors affecting battery performance, the research and development and optimization of negative electrode materials are crucial. Among the many negative electrode materials, silicon is considered an ideal choice for improving battery energy density because of its extremely high theoretical specific capacity (about 4200mAh / g), which is 10 times higher than the traditional carbon negative electrode (372mAh / g), and has better lithium insertion and release potential. However, the silicon negative electrode encounters a huge volume change problem (about 300%) in practical applications. Expansion / contraction stress will be generated during the lithium insertion / de-lithiation process, causing severe cracking of the silicon, resulting in the formation of an unstable SEI film on the silicon surface and consumption of active lithium ions, resulting in rapid capacity loss and low initial coulombic efficiency.

[0004] According to research, graphite and porous carbon in the negative electrode material have small volume changes during the lithiation process, and have good cycle stability and conductivity. For example, the volume expansion rate of graphite is about 10.6%. Compared with silicon, carbon materials have similar properties and they can be tightly combined with each other. Therefore, silicon-carbon negative electrodes have been widely studied due to their higher capacity, better conductivity and cycle stability.

[0005] The application of spray drying technology in industry has a history of more than 100 years. At first, due to the low thermal efficiency of this process, it was limited to the production of a few products such as milk powder. With the continuous research and development of this technology, it has been widely used in the chemical industry, food industry and other fields. High-speed centrifugal spray dryer is a process that uses centrifugal force to atomize liquid into micron-sized droplets, and then enters the drying tower for drying. In the centrifugal atomizer, the slurry, binder and other ingredients are sprayed into a rotating nozzle so that they are ejected outward at a very high speed to form particles. High-speed centrifugal spray dryer has the advantages of high efficiency and low energy consumption.

[0006] Therefore, there is an urgent need to provide a lithium ion battery silicon-carbon negative electrode material and a preparation method thereof to solve the above problems. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings and defects of the prior art and provide a lithium-ion battery silicon-carbon negative electrode material and a preparation method thereof, which significantly improves the overall performance of the battery and reduces the production cost.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a lithium-ion battery silicon-carbon negative electrode material comprises the following steps:

[0010] Step 1, evenly dispersing nano silicon slurry, graphite and binder in anhydrous ethanol according to a certain mass percentage to obtain silicon-carbon slurry;

[0011] Step 2, spray drying the silicon-carbon slurry to obtain silicon-carbon mixed particles;

[0012] Step 3: Mix the silicon-carbon mixed particles with either asphalt powder or phenolic resin powder, coat them in an inert gas, and then crush and sieve the coated silicon-carbon material to obtain a lithium-ion battery silicon-carbon negative electrode material.

[0013] As a preferred technical solution of the present invention, the mass percentage of each component in the silicon-carbon slurry is: nano-silicon slurry accounts for 5-40%, graphite accounts for 10-90%, and binder accounts for 1-5%. The sum of the mass percentages of each component is 100%, and the solid content of the silicon-carbon slurry after mixing is 5-40%.

[0014] As a preferred technical solution of the present invention, the particle size of the nano-silicon slurry is 0.1-5 μm, the graphite is one of graphite powder, natural graphite powder, and sand-ground graphite slurry, and the particle size of the graphite is 3-30 μm.

[0015] As a preferred technical solution of the present invention, the binder is one of melamine and phenolic resin.

[0016] As a preferred technical solution of the present invention, in step 2, the spray granulation inlet temperature is 180-220°C, the outlet temperature is 80-105°C, the fan frequency is 30-45HZ, the feed rate is 20-45%, and the atomizer frequency is 200HZ~400HZ.

[0017] As a preferred technical solution of the present invention, in step 3, the particle size of the asphalt powder is 3-20 μm, the mass ratio of the silicon-carbon mixed particles to the asphalt powder is 1:0.05-0.5, and the coating temperature is 4-8h.

[0018] As a preferred technical solution of the present invention, in step 3, the particle size of the phenolic resin powder is 3 to 20 μm, the mass ratio of the silicon-carbon mixed particles to the phenolic resin powder is 1:0.05 to 0.5; the coating temperature is 700 to 1000°C; and the coating time is 4 to 8 hours.

[0019] As a preferred technical solution of the present invention, in step 3, the inert gas is nitrogen, and the particle size of the coated silicon-carbon material is 9 to 22 μm.

[0020] The present invention also provides a lithium ion battery silicon-carbon negative electrode material prepared by the above-mentioned lithium ion battery silicon-carbon negative electrode material preparation method.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention prepares lithium-ion battery silicon-carbon negative electrode materials by adopting high-speed centrifugal spray granulation technology, thereby shortening the production cycle and improving production efficiency; by coating the silicon-carbon material with asphalt powder or phenolic resin powder, the volume expansion problem of the silicon material during the charging and discharging process is effectively improved, and the cycle stability and service life of the battery are significantly improved. Anhydrous ethanol is used as a solvent in the preparation process, and the solvent recovery rate is high, which effectively reduces the production cost. The lithium-ion battery silicon-carbon negative electrode material prepared by the present invention has stable and reliable quality, significantly improves the overall performance of the battery, and reduces the production cost at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of the steps of the preparation method.

[0024] Figure 2 This is a SEM image of the lithium-ion battery silicon-carbon negative electrode material prepared in Example 1 of the present invention.

[0025] Figure 3 This is a cycle performance diagram of the lithium-ion battery silicon-carbon negative electrode material prepared in Example 1 of the present invention at a current density of 0.1C.

[0026] Figure 4 This is a SEM image of the lithium-ion battery silicon-carbon negative electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0028] The specific implementation process of the present invention is as follows:

[0029] Reference Figure 1 , a method for preparing a lithium-ion battery silicon-carbon negative electrode material, comprising:

[0030] Nano-silicon slurry, graphite and binder are uniformly dispersed in anhydrous ethanol according to a certain mass percentage to obtain silicon-carbon slurry; the obtained silicon-carbon slurry is spray-dried and granulated in a dryer, and various conditions of the dryer are adjusted to obtain silicon-carbon mixed particles under optimal conditions; the obtained silicon-carbon mixed particles are mixed and coated with either asphalt powder or phenolic resin powder in a coating machine, and nitrogen protection is used, and the coated silicon-carbon material is crushed and sieved to obtain lithium-ion battery silicon-carbon negative electrode material.

[0031] The lithium-ion battery silicon-carbon negative electrode material prepared by the above-mentioned preparation method is used in the energy storage field and in lithium-ion batteries.

[0032] The present invention prepares lithium-ion battery silicon-carbon negative electrode materials through high-speed centrifugal spray drying granulation technology. Compared with other granulation technologies, the steps are simplified and the production complexity is greatly reduced. The wet material is quickly converted into dry particles by a high-speed centrifugal spray dryer, which shortens the production cycle and is easy to operate. The coated silicon-carbon negative electrode material can effectively alleviate the volume expansion problem of silicon during the charging and discharging process, thereby maintaining the stability of the battery capacity. The silicon-carbon particles prepared by high-speed centrifugal spray drying technology have uniform particle size, regular morphology, high particle quality, and significantly improve the overall performance of the battery. Due to the good solubility and high recovery rate of anhydrous ethanol, by using anhydrous ethanol as a solvent, the solvent recovery rate can reach more than 95%, thereby reducing production costs.

[0033] The lithium-ion battery silicon-carbon negative electrode material prepared by the present invention has stable and reliable quality, significantly improves the overall performance of the battery, and reduces production costs.

[0034] The present invention will be further described below in conjunction with specific embodiments.

[0035] Example 1

[0036] The nano silicon slurry with a particle size of 0.167 μm after sand grinding, the graphite slurry with a particle size of 6 μm and melamine are mixed evenly to obtain a silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 9.7%, graphite slurry accounts for 87.3%, melamine accounts for 3%, and the solid content of the mixed silicon-carbon slurry is 12%;

[0037] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 102°C, a fan frequency of 40HZ, a feed rate of 30%, and an atomizer frequency of 300HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 95%;

[0038] The granulated silicon-carbon mixed particles were mixed and coated with asphalt powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to asphalt powder was 10:1. The coating temperature was 700°C. Nitrogen was used for protection. The coated silicon-carbon material was crushed and sieved to obtain a finished lithium-ion battery silicon-carbon negative electrode material. The particle size of the finished lithium-ion battery silicon-carbon negative electrode material was 20 μm. Figure 2 SEN graph and Figure 3 The cycle performance diagram of the silicon-carbon negative electrode material for a lithium-ion battery at a current density of 0.1C shows that the lithium-ion battery silicon-carbon negative electrode material prepared by the preparation method of the present invention has good cycle performance and stable capacity.

[0039] Example 2

[0040] Graphite powder with a particle size of 3 μm is evenly dispersed in anhydrous ethanol, and then mixed evenly with nano silicon slurry with a particle size of 0.167 μm after sand grinding and melamine to obtain silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 9.7%, graphite slurry accounts for 87.3%, melamine accounts for 3%, and the solid content of the mixed silicon-carbon slurry is 23%;

[0041] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 102°C, a fan frequency of 38HZ, a feed rate of 30%, and an atomizer frequency of 330HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 95%;

[0042] The granulated silicon-carbon mixed particles are mixed and coated with asphalt powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to asphalt powder is 10:1. The coating temperature is 700°C. Nitrogen is used for protection. The coated silicon-carbon material is crushed and sieved to obtain a finished lithium-ion battery silicon-carbon negative electrode material. The particle size of the finished lithium-ion battery silicon-carbon negative electrode material is 18 μm.

[0043] Example 3

[0044] Graphite powder with a particle size of 3 μm is evenly dispersed in anhydrous ethanol, and then mixed evenly with nano silicon slurry with a particle size of 0.167 μm after sand grinding and melamine to obtain silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 9.7%, graphite slurry accounts for 87.3%, melamine accounts for 3%, and the solid content of the mixed silicon-carbon slurry is 23%;

[0045] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 100°C, a fan frequency of 38HZ, a feed rate of 30%, and an atomizer frequency of 280HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 97%;

[0046] The granulated silicon-carbon mixed particles were mixed and coated with asphalt powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to asphalt powder was 10:0.5. The coating temperature was 700 °C. Nitrogen protection was used. The coated silicon-carbon material was crushed and sieved to obtain the finished lithium-ion battery silicon-carbon negative electrode material. Figure 4 The particle size of the finished lithium-ion battery silicon-carbon negative electrode material is 18μm.

[0047] Example 4

[0048] Graphite powder with a particle size of 3 μm is evenly dispersed in anhydrous ethanol, and then mixed evenly with nano silicon slurry with a particle size of 0.167 μm after sand grinding and melamine to obtain silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 10%, graphite slurry accounts for 87.3%, melamine accounts for 2.5%, and the solid content of the silicon-carbon slurry after mixing is 16%;

[0049] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 99°C, a fan frequency of 42HZ, a feed rate of 30%, and an atomizer frequency of 300HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 95%;

[0050] The granulated silicon-carbon mixed particles are mixed and coated with phenolic resin powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to phenolic resin powder is 10:1. The coating temperature is 1000°C. Nitrogen protection is used. The coated silicon-carbon material is crushed and sieved to obtain a finished lithium-ion battery silicon-carbon negative electrode material. The particle size of the finished lithium-ion battery silicon-carbon negative electrode material is 19 μm.

[0051] Example 5

[0052] Graphite powder with a particle size of 3 μm is evenly dispersed in anhydrous ethanol, and then mixed evenly with nano silicon slurry with a particle size of 0.167 μm after sand grinding and melamine to obtain silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 9.7%, graphite slurry accounts for 87.3%, melamine accounts for 3%, and the solid content of the silicon-carbon slurry after mixing is 16%;

[0053] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 100°C, a fan frequency of 42HZ, a feed rate of 30%, and an atomizer frequency of 300HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 96%;

[0054] The granulated silicon-carbon mixed particles are mixed and coated with phenolic resin powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to phenolic resin powder is 10:0.5. The coating temperature is 900°C. Nitrogen protection is used to crush and sieve the coated silicon-carbon material to obtain a finished lithium-ion battery silicon-carbon negative electrode material. The particle size of the finished lithium-ion battery silicon-carbon negative electrode material is 189 μm.

[0055] Example 6

[0056] The nano silicon slurry with a particle size of 0.167 μm after sand grinding, the graphite slurry with a particle size of 6 μm and melamine are mixed evenly to obtain a silicon-carbon slurry; the mass percentage of each component in the silicon-carbon slurry is: nano silicon powder accounts for 9%, graphite slurry accounts for 88%, melamine accounts for 3%, and the solid content of the silicon-carbon slurry after mixing is 20%;

[0057] The silicon-carbon slurry was spray-dried and granulated in a spray dryer, with an inlet temperature of 200°C, an outlet temperature of 100°C, a fan frequency of 45HZ, a feed rate of 35%, and an atomizer frequency of 300HZ to obtain silicon-carbon mixed particles with an alcohol recovery rate of 95%;

[0058] The granulated silicon-carbon mixed particles are mixed and coated with asphalt powder with a particle size of 5 μm in a coating machine. The mass ratio of silicon-carbon particles to asphalt powder is 10:1. The coating temperature is 700°C. Nitrogen protection is used to crush and sieve the coated silicon-carbon material to obtain a finished lithium-ion battery silicon-carbon negative electrode material. The particle size of the finished lithium-ion battery silicon-carbon negative electrode material is 20 μm.

[0059] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material for a lithium-ion battery, characterized in that: The following steps are involved: Step 1, evenly dispersing nano silicon slurry, graphite and binder in anhydrous ethanol according to a certain mass percentage to obtain silicon-carbon slurry; Step 2, spray drying the silicon-carbon slurry to obtain silicon-carbon mixed particles; Step 3: Mix the silicon-carbon mixed particles with either asphalt powder or phenolic resin powder, coat them in an inert gas, and then crush and sieve the coated silicon-carbon material to obtain a lithium-ion battery silicon-carbon negative electrode material.

2. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: The mass percentages of the components in the silicon-carbon slurry are: 5-40% of nano-silicon slurry, 10-90% of graphite, and 1-5% of binder. The sum of the mass percentages of the components is 100%. After mixing, the solid content of the silicon-carbon slurry is 5-40%.

3. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 2, characterized in that: The particle size of the nano-silicon slurry is 0.1-5 μm, the graphite is one of graphite powder, natural graphite powder and sand-ground graphite slurry, and the particle size of the graphite is 3-30 μm.

4. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: The binder is one of melamine and phenolic resin.

5. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In the step 2, the spray granulation inlet temperature is 180-220° C., the outlet temperature is 80-105° C., the fan frequency is 30-45 Hz, the feed rate is 20-45%, and the atomizer frequency is 200 Hz to 400 Hz.

6. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In step 3, the particle size of the asphalt powder is 3-20 μm, the mass ratio of the silicon-carbon mixed particles to the asphalt powder is 1:0.05-0.5, and the coating temperature is 4-8 hours.

7. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In step 3, the particle size of the phenolic resin powder is 3 to 20 μm, the mass ratio of the silicon-carbon mixed particles to the phenolic resin powder is 1:0.05 to 0.5; the coating temperature is 700 to 1000° C.; and the coating time is 4 to 8 hours.

8. The method for preparing a lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In the step 3, the inert gas is nitrogen, and the particle size of the coated silicon-carbon material is 9 to 22 μm.

9. A lithium-ion battery silicon-carbon negative electrode material, characterized in that: The material is prepared by the method for preparing a lithium-ion battery silicon-carbon negative electrode material according to any one of claims 1 to 8.